Analysis Of Status KEK Pregnant Mother Towards Weight Low Body Event (LBW) In Manggari Puskesmas Kuningan District, 2019 - Usep Rusependhi; Diah Mulyawati Utari (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
Babies born at LBW (Low Body Event) are at risk of disrupting the growth and development of the baby, as well as the occurrence of hypertension, heart disease and diabetes in old age. One of the factors causing LBW is the condition of CED (Chronic Energy Deficiency) experienced by mothers during pregnancy. The highest prevalence of LBW in Kuningan Regency in 2018 is in the working area of the Manggari Community Health Center, which is 11.8% with the prevalence of pregnant women CED 10.1%. The purpose of this study was to determine the relationship of maternal CED status during pregnancy with LBW events. The study design uses case control from cohort registers of pregnant women. The total sample of the study were 114 infants, consisting of 38 cases and 76 controls who met the inclusion and exclusion criteria. The results of the statistical analysis of the Chi-Square test, obtained p value = 0.002 and OR = 4.317 (95% CI: 1.776-10.495) which means that there is a significant relationship between the status of CED during pregnancy with LBW events, where pregnant women CED risk 4.317 times higher for LBW delivery compared to pregnant women who are not CED. The conclusion of this study is that there is a relationship between the status of CED of mothers during pregnancy with the incidence of LBW.